2008
DOI: 10.1021/jo8021567
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Wolff Rearrangement of Cyclic 2-Diazo-1,3-Diketones: An Eco-compatible Route to α-Carbonylated Cycloalkanones

Abstract: The microwave-assisted Wolff rearrangement of cyclic 2-diazo-1,3-diketones performed in the presence of a stoichiometric amount of alcohol, amine, or thiol is an efficient, user, and environmentally friendly synthetic protocol for the synthesis of alpha-carbonylated cycloalkanones. This approach proves superior to existing protocols in scope and eco-compatibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…23 Recently, it was demonstrated that such a rearrangement could occur under dielectric heating (microwave irradiation), and that the transient acylketene can be trapped in a domino process with a variety of nucleophiles including alcohols, amines or thiols in nearly quantitative yields to provide a general access to α-carbonylated cycloalkanones (Scheme 10). 24 This approach allowed the easy introduction of chiral auxiliaries (35 and 37 for example), the preparation of otherwise difficultly available compounds (33, 35 and 36 for example), and overall, proved superior to existing approaches in scope and eco-compatibility. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Recently, it was demonstrated that such a rearrangement could occur under dielectric heating (microwave irradiation), and that the transient acylketene can be trapped in a domino process with a variety of nucleophiles including alcohols, amines or thiols in nearly quantitative yields to provide a general access to α-carbonylated cycloalkanones (Scheme 10). 24 This approach allowed the easy introduction of chiral auxiliaries (35 and 37 for example), the preparation of otherwise difficultly available compounds (33, 35 and 36 for example), and overall, proved superior to existing approaches in scope and eco-compatibility. …”
Section: Methodsmentioning
confidence: 99%
“…We can highlight here the recent utilization of malonyl dichloride in the key step of a synthetic approach to the polyprenylated phloroglucinol natural product clusianone (24, Scheme 7). Thus, the highly functionalized bicyclo[3.3.1]nonane framework of the natural product can be obtained in a single synthetic operation from the reaction of the silyl enol ether 22 with malonyl dichloride, a precursor of chloroacylketene, to give 23, which was then converted to clusianone (24) in few steps.…”
Section: Other Reactivity Of 13-dicarbonyl Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different approaches considered, microwaves are clearly the most largely used technique. Representative examples are the generation of ammonia from formamide (see Scheme 6(a), for the synthesis of N-heterocycles) (59), the nucleophilic substitution in aromatics (60), and the Wolff rearrangement of diazoketones (see Scheme 6(b)) (61).…”
Section: Analysis Of the Investigated Topicsmentioning
confidence: 99%
“…In addition, the 2-indanone derivative 5 l proved to be a particularly appropriate substrate for this metal-catalyzed cycloisomerization, thus leading efficiently to the polycylic alcohol 6 l in almost quantitative yield (entry 5). The allenic compound 5 m, having a strained cyclobutanone moiety, [11] was also cleanly Scheme 1. Reactivity of cyclic allenic ketones.…”
mentioning
confidence: 99%